Potensi dan tingkat pemanfaatan ikan layang (Decapterus sp) di perairan Makassar (Potential and level of utilization mackerel scad (Decapterus sp) in Makassar waters) - Suwarni Suwarni; Reski Fadilah (Program Studi Manajemen Sumber Daya Perairan, 2020)
Mackerel scad (Decapterus sp) is one type of pelagic fish whose sustainability is threatened. This study aims to determine the peak abundance of mackerel scad per week from May to July, production from 2007 to 2015, sustainable potential, optimum effort, TAC and utilization rate of mackerel scad. This research is expected to be considered in the management of mackerel scad. This research was conducted in May - July 2018. The research location was in the TPI Paotere office in Makassar. The method used in this research is survey and observation methods. Data collected in the form of primary data using observation and interviews as well as secondary data in the form of periodic data on catches and catch attempts from 2007-2015. To estimate the maximum sustainable yield of fisheries resources and optimal fishing efforts used in the Schaefer model, the data obtained will be analyzed to estimate and graph fishing efforts, and the level of mackerel scad resources in Makassar waters. MSY of mackerel scad obtained was 10,414.92 tons with optimal effort (fMSY) of 38,207.05 trips and permitted catches (TAC) of 8,331.94 tons. The average utilization rate is 73%.Keywords : Mackerel scad, MSY, fMSY, TAC, utilization rate.